PostCOVID-19 Impact on Perinatal Outcomes - Gaukhar Kurmanova; Ardak Ayazbekov; Almagul Kurmanova; Madina Rakhimbayeva; Gulzhan Trimova; Anarkul Kulembayeva (Diagnostics)
Background. Severe Acute Respiratory Syndrome-Related Coronavirus 2 (SARS-CoV-2) infection during pregnancy was associated with a number of adverse pregnancy outcomes, including miscarriage, preeclampsia, preterm birth, and stillbirth. The virus persistence can last for a long time, and the consequences of a previous coronavirus infection are currently under study. Objectives. This study aimed to establish the clinical features of the course of pregnancy and childbirth in women with a history of asymptomatic coronavirus disease 2019 (COVID-19). Methods. This study was conducted in the Regional Perinatal Center N3 of Turkestan city, Kazakhstan. A total of 229 participants were enrolled comprising individuals with (n = 133, exposed group) from August to September 2021 with a history of COVID-19 and without one in the same period in 2019 (n = 96, unexposed group). Results. There is a statistically significant strong association between a history of COVID-19 and the development of oligohydramnios (φ = 0.743, p < 0.001), and medium strength between a history of COVID-19 and the presence of anemia (φ = 0.254, p < 0.001), abnormal development of the placenta (φ = 0.254, p < 0.011), cord entanglement (φ = 0.343, p = 0.000), low birth weight (φ = 0.356, p < 0.001) and stillbirth (φ = 0.293, p < 0.001). Conclusions. The past COVID-19 infection in pregnant women has long-term consequences in the form of placenta abnormal development and oligohydramnios; and, as a result, the development of adverse perinatal outcomes